Aspects of the Health Inspection Authority in the People's Republic of China Health policies, systems and management - Ma, S.; Chen, G.; Tan, Boon-Kiang (BioMed Central Ltd., 2015)
Background: In China, there was a pressing need to establish a governmental agency to oversee the organizations that provide public health and medical services. The Chinese Health Inspection Authority (HIA), a relatively independent organization functioning at each administrative level (provincial, municipal, and county), was mandated to conduct 11 health inspection functions to maintain efficient public health and medical services. These functions include issuing health permit, conducting health supervision and inspection, health testing and evaluation, case investigation, complaint handling, managing public health crisis, monitoring and safeguarding public health at major public events, enforcing supervision and inspection compliance, public health education, information management, and team training and management. Since the reform of the health inspection system by the Ministry of Health in 2000, the HIA underwent a series of changes and transitions. This study aimed to describe and assess the five factors that were considered to be important for meeting service delivery objectives of the HIA in the People’s Republic of China. Methods: A total of 604 HIAs, sampled across three geographical regions of China at three administrative levels, participated in a cross-sectional survey conducted in 2013. Descriptive statistics were used to analyze the status of mandated operations, manpower, revenue and expenditures, and institutional infrastructure. Differences in these characteristics across the geographical regions and administrative levels were compared.Results: On average, the HIAs had not fully implemented the 11 mandated functions at any administrative levels. Governmental financial allocations were the main sources of revenue. Three primary personnel employment models coexisted and most employed the quasi-civil service employment model. The institutional infrastructure did not meet governmental mandated standards with respect to building area or the number and types of equipment available to conduct key functions. Conclusions: In 2012, the majority of the HIAs in China at the provincial, municipal, and county levels did not meet the mandated requirements, although positive indications toward meeting these requirements were observed. It is necessary for the government to pay more attention to institutional resources (buildings, equipment, and the level of the staff’s educational attainment) and ensure that the HIAs can meet their service delivery objectives.